WITTGENSTEIN AND PHILOSOPHICAL SPIRITUALITY IN THE LIGHT OF THE LECTURE ON ETHICS (Nóema, 2016)
The goal of  this paper is to provide a reading and interpretation of  one of Ludwig Wittgenstein’s less known writings, the Lecture on Ethics. My understanding of the Lecture is inspired by the interpretation of Wittgenstein’s philosophy  delivered by Pierre Hadot. In fact, what I will argue for is that the entire Lecture on Ethics can be seen as a so-called ‘Spiritual Exercise’. Following Hadot, I will argue that the Lecture's first purpose is to change the way we relate ourselves to the world or, in other words, our ethical attitude and behaviour toward it. Such, I believe, is not just the goal of a Spiritual Exercise, but also the broader focus of the austrian philosopher’s activity: that is, to engage the listener/reader causing him to consider and possibly revise his way of life, as regards the whole sphere that falls under the category of Ethics.
Keywords: Ludwig Wittgenstein; Pierre Hadot; Spiritual Exercises; Lecture on Ethics; Ethics